Pengaruh Kepimpinan Dalam Dasar Luar Malaysia - Ramli Dollah; Wan Shawaluddin Wan Hassan (Penerbit Universiti Malaysia Sabah, 2014)
The characteristic of foreign policy are determined by the leader of a country. The role of the leader, especially the chief executive of the state is very important in determining how a country’s foreign policy will be formulated according to its national interests. In this aspect, the character and perception of the leader are very important in influencing and determining the orientation of the policy or foreign policy of the state. This article focuses on the role of the Malaysia’s prime minister from Tunku to Najib in conducting foreign policy. Each of these leaders has demonstrated their enthusiasm and wisdom in conducting Malaysia’s foreign policy. This article concludes that from the Tengku’s pro-Western policy, Tun Razak’s non-align policy, the continuation of the policy under Tun Hussein, Mahathir’s confrontational posture, accommodative policy under Abdullah and Najib’s pragmatic policy, clearly indicate the crucial role of state’s leader in conducting Malaysia’s foreign policy and to pursue its national interests that has successfully projected Malaysia in international arena.